2018
DOI: 10.1155/2018/2157434
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Inflammatory Response to LPS in Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is a severe health problem worldwide, reaching epidemic levels. High susceptibility to infections of T2DM patients indicates dysregulated immune responses to pathogens. However, innate immune responses, including monocyte functions, in T2DM are poorly investigated. Therefore, in this study we aimed to assess lipopolysaccharide- (LPS-) induced immune responses of circulating monocytes from T2DM patients. The results showed that monocytes from T2DM were hyporesponsive to LPS chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
(42 reference statements)
2
23
1
Order By: Relevance
“…DAVID analyses do not take into consideration the direction of change in gene expression, but significantly enriched gene ontology terms from BM-derived and wound-derived Gr-1 þ cells also showed overlap of a number of terms ( Supplementary Table S1, highlighted in yellow) relating to leukocyte activation. This is consistent with previous reports showing aberrant activation (both hyper-and hyporesponsiveness) in a variety of myeloid cell subsets in diabetic patients and animal models (Bannon et al, 2013;Khondkaryan et al, 2018;Miao et al, 2012;Mirza and Koh, 2011;Satoh et al, 2010).…”
Section: Gene Expression Profiling Of Bm-derived and Wound-derived Grsupporting
confidence: 93%
See 1 more Smart Citation
“…DAVID analyses do not take into consideration the direction of change in gene expression, but significantly enriched gene ontology terms from BM-derived and wound-derived Gr-1 þ cells also showed overlap of a number of terms ( Supplementary Table S1, highlighted in yellow) relating to leukocyte activation. This is consistent with previous reports showing aberrant activation (both hyper-and hyporesponsiveness) in a variety of myeloid cell subsets in diabetic patients and animal models (Bannon et al, 2013;Khondkaryan et al, 2018;Miao et al, 2012;Mirza and Koh, 2011;Satoh et al, 2010).…”
Section: Gene Expression Profiling Of Bm-derived and Wound-derived Grsupporting
confidence: 93%
“…A more recent study in mice showed that genetic ablation of myeloid cells impaired wound healing, which again was associated with increased accumulation of neutrophils (Lucas et al, 2010;Mirza et al, 2009). Recent studies in human patients with diabetes showed an association with increased inflammatory cytokines in the circulation and a failure of myeloid cells isolated from these patients to respond to further stimulation (Khondkaryan et al, 2018). Altogether these studies and the data presented here support the idea that the diabetic environment induces a highly proinflammatory phenotype in myeloid cells during differentiation in the BM, inducing a tolerance-like phenotype, which upon challenge results in a reduced response, leading to a chronic inflammatory phenotype and impaired wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Our results further demonstrated the increased expression of the inflammatory cytokines in db/db mice. One of the main triggers of inflammation in diabetes is the gut microbiota, such as LPS [30]. LPS is the inflammatory component of the cell wall of the gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TLR2 and TLR4 further declines in diabetes patients with pneumonia. 26,27 Monocytes and macrophages can directly phagocytose pathogens. The phagocytic and killing capability of alveolar macrophages from diabetic mice decreased.…”
Section: Dovepressmentioning
confidence: 99%